If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -1(-9) = 7.9 Multiply -1 * -9 x + 9 = 7.9 Reorder the terms: 9 + x = 7.9 Solving 9 + x = 7.9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + x = 7.9 + -9 Combine like terms: 9 + -9 = 0 0 + x = 7.9 + -9 x = 7.9 + -9 Combine like terms: 7.9 + -9 = -1.1 x = -1.1 Simplifying x = -1.1
| 0.2xd+3=4 | | 4c+2p=45 | | 3x^2-13x+36=0 | | h=16t^2+40t+5 | | m^2+2m-575=0 | | 8x^4-20x^3-8x^2+20x=0 | | (a+3b)(2a-5b)= | | 9m+30=33 | | 6x(6x-5)-3(5-6x)= | | x^2+23-39=0 | | 16z^4-81z^4=0 | | a^2+6a+36=0 | | 6+ln(x+5)=8 | | Xsquared+5cubed=9cubed | | 9x^4-16=10x^2-17 | | 8x-18=36-6x | | 3*(15-x)=18 | | 2(3x-1)=4 | | 3*(x-15)=18 | | 5(7m-3)=14(2m+5) | | 3*(x-15)=48 | | V=6(8x+2)(5x-4)-10(5x-4) | | (2y-1)dy=(3x^2+1)dx | | 4x=190 | | (2y-1)dy=(3x+1)dx | | 2ln(5x+1)=14 | | 12a-11=15a-10 | | 10z+4=1 | | 3(x+4)-12x=48 | | lnx=70.0173683 | | 2q+5y+4z=0 | | 8h-24=36 |